Implementasi Media Game Puzzle dalam Meningkatkan Pemahaman Konsep Fonologi Materi Persukuan Kata pada Siswa Kelas Awal di Madrasah Ibtidaiyah - Fitriyah, Camilyatul; Ilyas, Muhammad; Yanuardianto, Elga (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
This study aims to explore the impact of using image-based puzzle games as a media to enhance students' understanding of phonological concepts related to word segmentation in early-grade students at an Islamic Elementary School (Madrasah Ibtidaiyah). The research adopts a Classroom Action Research (CAR) approach with a qualitative method. Data were collected through observation, interviews, documentation, and field notes during the teaching and learning process. Data analysis was conducted descriptively and interpretively through reduction, presentation, and conclusion drawing phases aligned with Miles and Huberman's model. The findings indicate that the implementation of image-based puzzle games significantly increased students' activeness, motivation, and comprehension of phonological concepts, especially in understanding word structure and the relationship between sounds and letters. The innovative use of this media helps students connect syllable forms with meanings visually and contextually, making the learning process more engaging and meaningful. This research provides valuable insights for educators to develop innovative, game-based instructional strategies suitable for elementary-level students.